Differences in Transdiaphragmatic Pressure of Dogs Suffering from Cervical or Thoracolumbar Myelopathy Anaesthetised with Isoflurane - Eirini Sarpekidou; Kyriaki Pavlidou; Ioannis Savvas; Zoe Polizopoulou; George Kazakos (Animals)
Background: The purpose of this study is to evaluate differences in transdiaphragmatic pressure (Pdi) in dogs suffering from cervical myelopathy (CM) and thoracolumbar myelopathy (TLM) anaesthetised with isoflurane (ISO). Methods: This prospective cohort study included ASA II-status dogs diagnosed with either CM or TLM, anaesthetised for diagnostic or surgical purposes between September 2021 and July 2023. Patients followed the same anaesthetic protocol, and maximum Pdi was recorded at 10 (Pdimax10), 20 (Pdimax20), and 30 (Pdimax30) minutes using balloon catheters placed in the stomach (Pgast) and in the mid-third of the oesophagus (Poes). Results: A total of 50 dogs were included: 25 in the CM group and 25 in the TLM group. In the TLM group, Pdimax10 was 9.4 mmHg ± 6.1, and in the CM group, it was 7.2 mmHg ± 4.6 (p = 0.167). Pdimax20 was 10.2 mmHg ± 5.8 in the TLM group and 8 mmHg ± 5.1 in the CM group (p = 0.155). Pdimax30 was 9.2 mmHg ± 5.5 in the TLM group and 8.1 mmHg ± 5.5 in the CM group (p = 0.479). Conclusions: The findings suggest that diaphragmatic contractility is similar in dogs with CM and TLM under ISO anaesthesia.